2021
DOI: 10.1177/00420859211068468
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Youth Sociopolitical Action: The Roles of Critical Reflection, Sociopolitical Efficacy, and Transformative Student Voice

Abstract: Critical pedagogies often prioritize critical thinking and social awareness at the expense of preparing urban youth for social action. Though sociopolitical efficacy is argued to bridge critical reflection and social action, this relationship is undetermined. We argue that critical reflection and sociopolitical efficacy are independent predictors of sociopolitical action. We surveyed 158 high-school students and found that critical reflection and sociopolitical efficacy were positively related to sociopolitica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…As Watts and Guessous (2006) stated “people take action when they believe they can make an impact” (p. 63). The literature supports the notion that sociopolitical efficacy positively links to social action (Diemer & Li, 2011; Hipolito‐Delgado et al., 2021; Hope & Jagers, 2014). Taking this idea even further, Poteat et al.…”
Section: Sociopolitical Developmentsupporting
confidence: 70%
See 2 more Smart Citations
“…As Watts and Guessous (2006) stated “people take action when they believe they can make an impact” (p. 63). The literature supports the notion that sociopolitical efficacy positively links to social action (Diemer & Li, 2011; Hipolito‐Delgado et al., 2021; Hope & Jagers, 2014). Taking this idea even further, Poteat et al.…”
Section: Sociopolitical Developmentsupporting
confidence: 70%
“…As Watts and Guessous (2006) stated "people take action when they believe they can make an impact" (p. 63). The literature supports the notion that sociopolitical efficacy positively links to social action (Diemer & Li, 2011;Hipolito-Delgado et al, 2021;Hope & Jagers, 2014). Taking this idea even further, Poteat et al (2020) found a reciprocal relationship between sociopolitical efficacy and action, as sociopolitical efficacy longitudinally predicted action and the action in turn reinforced sociopolitical efficacy in youth who were members of gay-straight alliances in schools.…”
Section: Sociopolitical Developmentsupporting
confidence: 60%
See 1 more Smart Citation
“…Studies tending to students’ academic development ( n = 4) found that school counselors may use YPAR to approach retention issues in mainstream and alternative education (Chou et al, 2015); to assess reading achievement, bolster attendance, and address problematic discipline referral rates (Voight & Velez, 2018); and to support students’ critical thinking (Stickl Haugen et al, 2019) and self-efficacy in STEM (Edirmanasinghe, 2020). Two articles pointed to the use of YPAR to simultaneously promote students’ social/emotional, academic, and/or career (i.e., holistic) development (Hipolito-Delgado et al, 2021, Williams et al, 2020). For example, the school counselor’s use of YPAR to amplify student voice can impact student’s socioemotional and academic development (Hipolito-Delgado et al, 2021).…”
Section: Results: How Can School Counselors Use Ypar Practices and Pa...mentioning
confidence: 99%
“…Two articles pointed to the use of YPAR to simultaneously promote students' social/emotional, academic, and/or career (i.e., holistic) development (Hipolito-Delgado et al, 2021, Williams et al, 2020. For example, the school counselor's use of YPAR to amplify student voice can impact student's socioemotional and academic development (Hipolito-Delgado et al, 2021). Despite YPAR's potential to foster academic, social/ emotional, and career development, focusing on transformative resistance is also important for school counselors.…”
Section: Outcomes/objectivesmentioning
confidence: 99%